Xylazine as a Drug of Abuse and Its Effects on the Generation of Reactive Species and DNA Damage on Human Umbilical Vein Endothelial Cells - Luz Silva-Torres; Christian Veléz; Lyvia Álvarez; Beatriz Zayas (Journal of Toxicology)
Human xylazine (XYL) abuse among addicts has received great interest due to its potential toxic effects upon addicts and the need to understand the mechanism of action associated with the potential health effects. XYL is an alpha-2 agonist restricted to veterinarian applications, without human medical applications. Our previous work demonstrated that XYL and its combination with cocaine (COC) and/or 6-monoacetylmorphine (6-MAM) induce cell death through an apoptotic mechanism. The aim of this study was to determine the effect of xylazine on the generation of reactive oxygen species (ROS) and reactive nitrogen species (RNS) as well as DNA damage on endothelial cell. Human umbilical vein endothelial cells (HUVEC) were treated with XYL (60 μM), COC (160 μM), 6-MAM (160 μM), camptothecin (positive control, 50 μM), XYL/COC (50 μM), XYL/6-MAM (50 μM), and XYL/COC/6-MAM (40 μM) for a period of 24 hours. Generation of intracellular ROS, RNS, and DNA fragmentation were analyzed using a fluorometric assay. Results reveal that XYL and 6-MAM increase levels of ROS; no induction of RNS production was observed. The combination of these drugs shows significant increase in DNA fragmentation in G2/M phase, while XYL, COC, and 6-MAM, without combination, present higher DNA fragmentation in G0/G1 phase. These findings support that these drugs and their combination alter important biochemical events aligned with an apoptotic mechanism of action in HUVEC.